Caracterização físico-química e produtiva de frutos e sementes e propagação de Eugenia calycina Camb. (Myrtaceae) - Borges, Kelly Cristiene de Freitas (2016)
Many native fruit species of the Cerrado biome have great food potential, however, in this respect, still very poorly studied. This research aimed to evaluate the physical-chemical and productive characteristics of fruits and seeds and propagation of Surinam Eugenia calycina, the Private Natural Heritage Reserve (RPPN) Hunt Club and Itororó Fishing, municipality of Uberlândia- GO. The readings to obtain the phenological data were always performed in the second ten days of each month. Biometrics fruit and seeds were carried out in 50 selected fruit materials collected at four separate locations in the area of RPPN. It was obtained length (mm) and width (mm) of the fruits and seeds using a digital caliper, and made to count the number of seeds per fruit. Seed germination test consisted of the evaluation of various types of substrates (A-screen, B-blotting; C-germitest, D-vermiculite; E-sand), in the School of Agronomy Seed Laboratory, Faculty of Philosophy and Human Sciences Goiatuba, municipality of Goiatuba, GO, Brazil. The seedling emergence test was installed in a greenhouse, adopting a randomized block design (RBD), with four treatments, corresponding to different locations of collections of fruits (1, 2, 3 and 4), with five repetitions totaling 20 plots. The test evaluation of vegetative propagation, adopted the factorial experimental design with three types of cuttings: basal, middle and apical, and six different times of soaking of the stakes in the Indole-butiric acid: 0.5 second, 15, 30, 45 and 60 seconds), with three replications and 10 cuttings per repetition. The evaluations were performed at 60 days after installation of the experiment. It was collected 300 g of fruit randomly at each location, as identified by the physical characteristics of the soil, considering the relationship clay/sands these locations. The fruit samples were sent to the Center for Food Research (CPA) for chemical analysis. All data were subjected to statistical tests as the characteristics of the collected data. Regarding the phenophases, E. calycina features flowering August to January, with the highest peak bloom, 75% and 100% in September and October respectively the fruits have widths ranging from 6 to 9 mm in different collection sites, and lengths of 14 to 30 mm; while the width of the seeds ranged from 5 to 7 mm and a length of 10 to 14 mm. Collected seeds in E. plant calycina established in soils with different proportions of clay and sand, do not differ in their potential to spread. The different immersion times and the IBA solution at a concentration of 6,000 mg L-¹ did not induce the rooting of cuttings of Surinam E. calycina. The fruits have nutritional importance by the presence of significant levels of minerals that contribute to human health, such as potassium, iron, manganese, magnesium and high percentage of Brix. Regarding the results of this study, it is recommended to carry out further research in relation to the species E. calycina urgently because its natural population has declined apace.